Effectiveness of a school-based mental health intervention for school teachers in urban Pakistan: a randomized controlled trial - Nazish Imran; Atif Rahman; Nakhshab Chaudhry; Aftab Asif (BMC, 2022)
Abstract Background Schools have a major role in promoting children's physical and psychological health and well-being and the mental health literacy of all key stakeholders, especially teachers, is critical to achieving this goal. Teachers' knowledge and beliefs about psychological problems influence the way they deal with their students' mental health issues. This study is a preliminary investigation evaluating the effectiveness and feasibility of a School Mental Health Programme (SMHP) developed by the World Health Organization's Eastern Mediterranean Regional Office (WHO-EMRO) in improving mental health literacy and self-efficacy among school teachers in an inner-city area of urban Lahore. Methods Teachers were randomly assigned to 3 days standardized WHO-EMRO School Mental Health Manual based Intervention (n = 118) or to a wait list delayed intervention control group (n = 113). Teachers were assessed pre and post training and at 3 months follow up using measures for mental health literacy (Primary outcome) and self-efficacy. School Heads completed the WHO School Psychosocial Profile and students reported socioemotional skills and psychological problems using Strengths and Difficulties questionnaire at baseline and 3 months post intervention. Results Compared with waitlist group, teachers in intervention group presented a significant increase in mental health literacy (F 2,181 = 8.92; P < 0.001), as well as better teacher's self-efficacy in classroom management and student engagement (F 2,181 = 16.45; P ≤ 0.000 and F 2,181 = 4.65; P ≤ 0.011, respectively). Increase confidence in helping students with mental health problems was also noted in the intervention arm (F 2,181 = 15.96 P ≤ 0.000). Improvement in overall school environment was also found. No statistical difference in the emotional and behavioural difficulties in students was noticed at 3 months. Conclusion This study is one of the first preliminary investigation of WHO-EMRO school mental health intervention in Pakistan. The study showed that intervention led to significant improvement in mental health literacy and self-efficacy among teachers, which was largely sustained over time. Despite a major limitation of lack of clustering and likely contamination affecting follow up outcomes, the study showed promising results in the context of mental health promotion, prevention and early intervention in schools in Lahore, Pakistan. A larger cluster randomised trial is justified, given the level of participant engagement and acceptability by schools. Trail Registration: ClinicalTrials.gov registry (NCT02937714) Registered 13th October 2016, https://register.clinicaltrials.gov .